محمد عاصم بٹ کے ناول "بھید "میں وجودیت: Existentialism in Muhammad Asim Butt’s Novel “Bhaid” (Al-Qamar, 2023)
In 20th century existentialism theory introduced in Europe in literature and decided to discuss the relations between individual and universe or creator. In Fiction writers like Albert Camus, Fyodor Dostoevsky, Jean- Paul Sartre, Frannz kaflea etc got fame in this context, specially, the stranger, and crime punishment, Nausea, respectively considered Master pieces. In subcontinent partition is third dilemma in addition to two World Wars. So the Question of existence of man arose after displacement and Continuity of colonialism in different forms. In Urdu Literature fiction writers also took it as subject but only few of them succeeded to apply existentialism theory in novels. Because, the techniques, require for this subject are, not easy. Muhammad Asim Butt influenced by Franz kafks in terms of style and technique. He wrote this novel in an absurdist, unorthodox and bizarre fashion. Apparently, the events described in simple language but between the lines multiple meaning is existed. Butt portrayed a multishade picture of our society. In this article efforts have been made to depict the reality lies in Bhaid.
Keywords: Existentialism; theory; Lahore; Culture; Asim